Using multimedia in developing Islamic website - Zeki, Akram M.; Badi, Maimona J. (IIUM Press, 2015)
The adoption of multimedia by online communication outlets has increased enormously. The most documented or common multimedia elements are photos, music, audio, and videos. Effective management of these multimedia elements is necessary for both private and public institutions along with individuals (Bainbrideg & Browne, 2005; Deborah & Charles, 2012). The faster connection and powerful processing capability has improved the content delivery and what is left now is a different interface design which must consider the interactivity and high impact of multimedia content. Moreover, these changes have caused the need to re-examine multimedia elements.